Impact of Work–Family Conflict, Job Stress and Job Satisfaction on Seafarer Performance - Ji An (International Journal of Environmental Research and Public Health, 2020)
A lack of research has been undertaken to explore work−family conflict and its impact on the shipping industry. The objective of the present study was to empirically examine the effects of work−family conflict, job stress, and job satisfaction on seafarer performance. Data were collected from merchant ship seafarers in the Yangshan Port, Shanghai, China (n = 337). A data analysis was performed using hierarchical regression analysis. The research results revealed that work−family conflict and job stress negatively affects seafarer self-reported performance, while job satisfaction positively influences seafarer job performance. Findings also show that job satisfaction plays a moderating role in the relationships between work−family conflict, job stress and seafarer performance. Our findings demonstrate that work−family conflict, job stress and job satisfaction manifested are significant predictors for seafarer performance. Important applications and implications are provided for managers and researchers.